Popularization of improved sunflower (Helianthus annuus L.) production technology through frontline demonstrations in non-traditional belts of West Bengal: POPULARIZATION OF SUNFLOWER PRODUCTION TECHNOLOGY THROUGH FLDs IN WEST BENGAL - S S LAKSHMAN; D PATI (Journal of Oilseeds Research, 2018)
The Front Line Demonstrations (FLDs) on modern approaches of sunflower cultivation was attempted during rabi season 2011-12 to 2013-14 on farmers' field in the non-traditional belts of West Bengal (Bankura and Purulia districts) under Tribal Sub-Plan Programme. The average seed yield of sunflower under demonstration plot was recorded 1875-2250 kg/ha compared to conventional rapeseed mustard cultivation where production was recorded 1000-1200 kg/ha. In West Bengal, the yield gaps between improved technology (full package of sunflower demonstration with best management practices) and farmers practice (rapeseed mustard cultivation through conventional approaches) was recorded 875-1050 kg/ha. The study recommends that the gross return and net return can be improved by adopting technologies viz., use of sunflower hybrids (DRSH-1, KBSH-44, KBSH-41, KBSH-53), adopting proper spacing and thinning, spraying of boron at ray floret stage and use of bio-inoculants for management of diseases.